A Mother's Journey: Finding Meaning While Raising a Child with Cerebral Palsy - Nurul Imaniana, Anisa; Maulana, Gamal (International Journal of Social Science, Education, Communication and Economics, 2024)
This study originates from the researcher's interest in a mother who has a child with cerebral palsy but is able to find meaning in life despite the challenges she faces. Being a mother to a child with developmental disabilities is not easy, yet the subject of this study strives to find meaning in every difficult experience. The purpose of this study is to understand how the subject, as a parent of a child with cerebral palsy, discovers meaning in life. Life's meaning encompasses what is considered important and valuable, providing special significance to an individual's life. This meaning can be found in both positive and negative circumstances, in happiness and suffering. The process involves realizing opportunities within certain situations and understanding what can be done. This qualitative study employs a descriptive case study design, with data collected through interviews and observations of a single subject. Data validity is ensured by also interviewing a significant other. The analysis reveals that the subject's meaning in life is reflected in her life goals, such as improving her living conditions, owning a house, and hoping her child becomes independent.